2012
DOI: 10.1021/bi300845s
|View full text |Cite
|
Sign up to set email alerts
|

Serine Phosphorylation Is Critical for the Activation of Ubiquitin-Specific Protease 1 and Its Interaction with WD40-Repeat Protein UAF1

Abstract: Deubiquitinating enzymes (DUBs) are important for the normal function of a number of cellular processes, including transcriptional regulation, cell cycle control, and DNA damage response. The enzymatic activity of DUB is regulated by different mechanisms. DUBs in several different families are post-translationally modified by phosphorylation. Large scale phosphoproteomic studies of human DUBs revealed that a majority of ubiquitin-specific proteases (USPs) are phosphorylated. USP1 is a prototypical DUB that req… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 58 publications
2
46
0
Order By: Relevance
“…2). Mapping the peptides to a modeled USP1 structure revealed that they are located outside the USP1 catalytic site 27 . The peptides comprising residues 412–448, 451–481, 524–563 and 553–566 are in the finger and palm domains that form the ubiquitin-binding site.…”
Section: Resultsmentioning
confidence: 99%
“…2). Mapping the peptides to a modeled USP1 structure revealed that they are located outside the USP1 catalytic site 27 . The peptides comprising residues 412–448, 451–481, 524–563 and 553–566 are in the finger and palm domains that form the ubiquitin-binding site.…”
Section: Resultsmentioning
confidence: 99%
“…Simpler instances of allosteric regulation are found with the increase in k cat following interaction of USP1, USP12, and USP46 with UAF1 (WDR48) (40, 41). However, the interaction between USP1 and UAF1 is itself regulated by CDK1-mediated serine phosphorylation of USP1 (267). The COOHterminal region of USP7 contains 5 Ubiquitin-like (Ubl) domains organized into 2-1-2 Ubl units, the last pair of which (HUBL-45) activate USP7 by 100-fold (66,71 (171,218).…”
Section: Regulation Of Dub Activitymentioning
confidence: 99%
“…Activation by phosphorylation also takes place during the cell cycle, where USP37 is modified by CDK-2 to directly stimulate DUB activity [74]. In an analogous manner, USP1 phosphorylation was suggested to be required for complex formation with the activator UAF-1 [75].…”
Section: Post-translational Modificationsmentioning
confidence: 99%